Practical Issues of Applying Ho Chi Minh’s Ethical Thought about Education and Training in Revolutionary Ethics for Party Members in the Party Committee of Can Tho City, Vietnam - Thanh, Luong Thi Hoai; Son, Nguyen Thai; Hung, Nguyen Thanh; Can, Bui Thi (Journal of Ecohumanism, 2024)
In Ho Chi Minh’s ideology, the issue of education and revolutionary moral training of cadres and party members has a particularly important position and role. In the process of globalization, international integration, and market economy, its negative and negative sides cause a part of cadres and party members to degrade in morality and lifestyle like today; therefore, education and training in revolutionary ethics for cadres and party members is both a basic, long-term, and urgent task for a prosperous and powerful Vietnam.